Pengaruh PENGARUH REPUTASI UNDERWRITER, REPUTASI AUDITOR, LEVERAGE, PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, LIFE STAGE PERUSAHAAN TERHADAP UNDERPRICING SAHAM PADA IPO DI BEI: - - -, Dian Retnaningdiah; Kurnianingsih, Retno; Pahlevi, Reza Widhar (Kajian Ekonomi dan Bisnis, 2024)
In Indonesia Stock Exchange, there is often an initial price of the shares offered is lower than the price on the first day of secondary market that called underpricing. This empirical study aimed to examine the effect of Underwriter Reputation, Auditors Reputation, Leverage, Profitability, Liquidity, firm size, and life stage of the firm on stock underpricing of initial public offering on the Indonesia Stock Exchange. Which methode used in these research is non probablity with purposive sampling.The population in this study is a company listed on the Indonesia Stock Exchange, with the periods of sampling is the year 2020 to 2023, obtained as many samples 57 emiten (companies) out of a population of 57 emiten. These research was conducted with using multiple linear regression analtysis with a significant level 5%.   The results show the variables Underwriter Reputation and Auditor Reputation have no significant effect on underpricing. Leverage variable positive and significant effect on the Underpricing. While variable profitability, Liquidity, firm Size, and life stage of the firm significantly and negatively related to the underpricing IPO shares on the Indonesia Stock Exchange.     Keywords:       Reputasi Underwriter, Reputasi Auditor, Leverage, Profitabilitas, Likuiditas, Ukuran Perusahaan, dan Life Stage Perusahaan Underpricing Saham, IPO,  Bursa Efek Indonesia